Newly identified variability of the antigen binding site coding sequences of the equine major histocompatibility complex class I and class II genes - Plasil, Martin; Oppelt, Jan; Klumplerova, Marie; Bubenikova, Jana; Vychodilova, Leona; Janova, Eva; Stejskalova, Karla; Futas, Jan; Knoll, Ales; Leblond, Agnes; Mihalca, Andrei D; Horin, Petr (HLA, 2023)
The major histocompatibility complex (MHC) with its class I and II genes plays a crucial role in the immune response to pathogens by presenting oligopeptide antigens to various immune response effector cells. In order to counteract the vast variability of infectious agents, MHC class I and II genes usually retain high levels of SNPs mainly concentrated in the exons encoding the antigen binding sites. The aim of the study was to reveal new variability of selected MHC genes with a special focus on MHC class I physical haplotypes. Long-range NGS to was used to identify exon 2-exon 3 alleles in three genetically distinct horse breeds. A total of 116 allelic variants were found in the MHC class I genes Eqca-1, Eqca-2, Eqca-7 and Eqca-Ψ, 112 of which were novel. The MHC class II DRA locus was confirmed to comprise five exon 2 alleles, and no new sequences were observed. Additional variability in terms of 15 novel exon 2 alleles was identified in the DQA1 locus. Extensive overall variability across the entire MHC region was confirmed by an analysis of MHC-linked microsatellite loci. Both diversifying and purifying selection were detected within the MHC class I and II loci analyzed.
Keywords: alely; MHC class I; exony; Equus caballus; Histocompatibility Antigens Class I; Horses; Alleles; Exons; vazebná místa; koně; zvířata; MHC; Binding Sites; geny MHC třídy II; MSATs; Eqca; Major Histocompatibility Complex; Genes, MHC Class II; hlavní histokompatibilní komplex; Animals; Histocompatibility Antigens Class II; MHC antigeny I. třídy; MHC antigeny II. třídy; MHC class II